2022
DOI: 10.1101/2022.01.28.478108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LmTag: functional-enrichment and imputation-aware tag SNP selection for population-specific genotyping arrays

Abstract: Despite the rapid development of sequencing technology, single-nucleotide polymorphism (SNP) array is still the most cost-effective genotyping solutions for large-scale genomic research and applications. Recent years have witnessed the rapid development of numerous genotyping platforms of different sizes and designs, but population-specific platforms are still lacking, especially for those in developing countries. We aim to develop methods to design SNP arrays for thse countries, so the arrays should be cost-e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For example, the Japonica Array NEO, and the UK Biobank Array showed the highest performance when comparing with other arrays with the same sizes for EAS, and EUR populations respectively. This indicates that using customized, small-size SNP arrays at population-specific level can be a cost-effective genotyping solution without loosing PGS performance (Tam et al, 2019; Nguyen et al, 2022). We also observed that there are no specific arrays with moderate sizes that had superior imputation performances in AFR, and SAS, suggesting the need for genotyping arrays optimized for these populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Japonica Array NEO, and the UK Biobank Array showed the highest performance when comparing with other arrays with the same sizes for EAS, and EUR populations respectively. This indicates that using customized, small-size SNP arrays at population-specific level can be a cost-effective genotyping solution without loosing PGS performance (Tam et al, 2019; Nguyen et al, 2022). We also observed that there are no specific arrays with moderate sizes that had superior imputation performances in AFR, and SAS, suggesting the need for genotyping arrays optimized for these populations.…”
Section: Discussionmentioning
confidence: 99%